Market Conditions and Worker Training: How Does it Affect and Whom? - Sumon Majumdar (Queen's University, Department of Economics, 2006)
This paper analyses the impact of labor market conditions on a firm's incentive to train its workers. In an equilibrium model of the labor market in which firms use both untrained and in-house trained workers, we show that the incidence of training increases with the tightness of the labor market. In a multi-sector framework, the usual threat of hold-up by a trained worker is more severe for workers who change their sector of work; during downturns, this serves to bias firms' incentives in imparting training away from such workers and towards workers already in the firm and those new workers coming from the same sector. Evidence from the NLSY confirms both predictions — the incidence and duration of company-sponsored training is adversely affected by higher unemployment rates; furthermore, this negative effect is much stronger for workers who change industries as compared to those who do not.
Keywords: J24; J31; J41; 330; firm-sponsored training; labor market tightness; hold up; unemployment rate; Arbeitsmarkttheorie; Betriebliches Bildungsmanagement; Betriebliche Ausbildung; Theorie